MANAGEMENT OF COMPLEX FISTULA IN ANO USING IFTAK (INTERSEPTION OF FISTULOUS TRACT AND APPLICATION OF KSHARASUTRA)-A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2020)
The conventional treatment for Fistula-in-ano (FIA) is arduous due to its high chance of recurrence and damage caused to anal sphincter during the surgery. In Ayurveda, FIA is treated with Ksharasutra which has high success rate of 96.67%. However, it has some limitations, so to overcome them, the Interception of fistulous tract with application of Kshara Sutra (IFTAK) technique has been suggested by the Ayurvedic surgeons for better success. In the present case study, 17 year old female visited our Centre who had significant medical history with chief complaint of blood mixed pus discharge with pain from perianal region. She had history of being operated twice for this complaint but got no satisfactory improvement. On local examination, she was diagnosed as case of FIA and planned for Ksharasutra by IFTAK. IFTAK procedure has taken less time as compared to conventional Ksharasutra procedure and has led to successful outcome. Months of follow up reveals no recurrence.